Circuits : engineering concepts and analysis of linear electric circuits - Carlson, A. Bruce (Pacific Grove, CA : Brooks/Cole, 2000)
This book is about: Circuit variables and laws; Properties of resistive circuits; Applications of resistive circuits; ...
Keywords: Electric circuits; Electric circuit analysis; Linear; Electric circuits, Linear; Electric circuit analysis